Spondyloenchondrodysplasia: a rare cause of short stature - Yeşiltepe-Mutlu, Gül; Özsu, Elif; Çizmecioğlu, Filiz Mine; Alanay, Yasemin; Hatun, Şükrü (The Turkish Journal of Pediatrics, 2011)
Skeletal dysplasias (osteochondrodysplasias) are a group of diseases that must be included in the differential diagnosis of disproportionate short stature. History, clinical and radiologic findings and consanguinity are important features to be considered when a specific diagnosis is investigated. Spondyloenchondrodysplasia is a very rare skeletal dysplasia characterized with enchondromas in the long bones and platyspondyly. Manifestation of the disorder may include neurological involvement (spasticity, intracranial calcifications and mental retardation) and immune dysfunction. Herein, we report a 12-year-old boy who admitted to our clinic with short stature, who was born to consanguineous parents. He presented clinical (significant widening of wrists, ankles and knees) and radiologic (enchondromatous lesions in the metaphysis of long bones) features of spondyloenchondrodysplasia but did not yet have neurologic or immunologic involvement.